Oestrogen facilitates the binding of ubiquitous and liver-enriched nuclear proteins to the apoVLDL II promoter in vivo. - Wijnholds, J (1991)
Using genomic and in vitro DNasel footprinting, we have analyzed protein-DNA interactions within the promoter region of the oestrogen-inducible gene encoding chicken apoVLDL II. The footprints coincide with previously detected guanosine-protein contacts in vivo. All footprints identified are present in the apoVLDL II-expressing liver exclusively and absent in hormone-naive liver, spleen and oviduct. They comprise recognition sites for the oestrogen receptor, the ubiquitous COUP-transcription factor, the liver-enriched C/EBP and/or DBP and the liver-specific LF-A1. In vitro, binding of protein to the oestrogen response element (ERE) is excluded by the prior binding of a protein, possibly C/EBP or DBP, to an adjacent element. The recognition sequence of the COUP-TF is also a target for LF-A1. The results suggests that oestrogen-dependent liver specific activation of the apoVLDL II promoter is established by the binding of the oestrogen receptor to EREs and multiple liver-enriched factors (C/EBP, DBP and LF-A1) to their nearby recognition sequences. Apparently, several DNA binding nuclear proteins cooperate to keep the promoter in a state that is accessible for the RNA polymerase complex.